2014
DOI: 10.1051/0004-6361/201423698
|View full text |Cite
|
Sign up to set email alerts
|

Blobs in recurring extreme-ultraviolet jets

Abstract: Context. Coronal jets are one type of ubiquitous small-scale activity that is caused by magnetic reconnection in the solar corona. They are often associated with cool surges in the chromosphere. Aims. In this paper, we report our discovery of blobs in the recurrent and homologous jets that occurred at the western edge of the NOAA active region 11259 on 2011 July 22. Methods. The jets were observed in the seven extreme-ultraviolet (EUV) filters of the Atmospheric Imaging Assembly instrument aboard the Solar Dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
74
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 87 publications
(105 reference statements)
14
74
0
3
Order By: Relevance
“…The plasmoids or blob-like structures are also reported in the spire during the evolution of the coronal jets as seen in observations and models (e.g., Zhang and Ji, 2014;Zhang, Ji and Su, 2016;Zhang and Zhang, 2017;Ni et al, 2017). These localized plasma blobs are formed at the junction of the jet-plasma spire and the base-arch field.…”
Section: Introductionmentioning
confidence: 67%
“…The plasmoids or blob-like structures are also reported in the spire during the evolution of the coronal jets as seen in observations and models (e.g., Zhang and Ji, 2014;Zhang, Ji and Su, 2016;Zhang and Zhang, 2017;Ni et al, 2017). These localized plasma blobs are formed at the junction of the jet-plasma spire and the base-arch field.…”
Section: Introductionmentioning
confidence: 67%
“…Once the flux ropes were ejected, new ones formed in their place, and the process was repeated as the jet proceeded. This repeated formation and ejection of plasma blobs provides a natural explanation for the intermittent outflows, bright blobs of emission, and quasiperiodic intensity fluctuations observed in some jets (e.g., Singh et al 2011Singh et al , 2012Morton et al 2012;Zhang & Ji 2014;Filippov et al 2015). The thread-like nature of the tearingmediated outflows may also explain the filamentary structure often observed in jets (e.g., Singh et al 2011;Cheung et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Recent Interface Region Imaging Spectrograph (IRIS) observations of an active-region jet revealed filamentary fine-scale structure in the emission from the reconnection region (Cheung et al 2015). Solar Dynamics Observatory observations have shown blobs forming in both small (Zhang & Ji 2014) and large (Filippov et al 2015) open-field EUV jets. Recent Solar TErrestrial RElations Observatory observations have also revealed trains of plasma blobs within jets in the closed-field corona near active regions (Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Chen et al (2013) studied the temperature structure of an AR jet using the same DEM method and find hot plasma ∼7 MK at the footpoint of jet. Zhang & Ji (2014) investigate the temperature of plasma blobs that were observed along the spire of a recurrent AR jet using the DEM method, "xrt_dem_iterative2.pro", along with Monte Carlo (MC) simulations (details in Cheng et al 2012). The authors find the DEM-weighted average temperatures of the three blobs to range from 0.5 to 4 MK with a median value of ∼2.3 MK, and the densities of 3.3, 1.9, and 2.1 × 10 9 cm −3 , respectively.…”
Section: Introductionmentioning
confidence: 99%